PEMANFAATAN SERBUK GERGAJI KAYU JATI (TECTONA GRANDIS L.F) SEBAGAI ADSORBEN LOGAM CU (II) - Gusti Ayu Arini; Sitti Aminah (Media Eksakta, 2020)
Sawdust is one of the industrial wastes that can be used as an absorbent. The chemical content in sawdust is the same as in its wood, i.e lignin, cellulose, and hemicellulose. This study aimed to determine the optimum contact time, optimum weight, and adsorption capacity of Cu (II) ions by teak sawdust using the atomic absorption spectrophotometry (AAS). Determination of optimum contact time was carried out with time variations of 10, 30 and 60 minutes, the optimum weight with various weight of 0.5, 1, and 1.5 grams, and the adsorption capacity of teak sawdust in various concentrations of 50, 100, 150 and 200 ppm. The results showed that the equilibrium contact time was reached at 30 minutes, and the percentage of adsorption of Cu (II) was 91.25%. The optimum weight for metal adsorption was 1.5 gram, and the adsorption percentage of adsorbed Cu (II) ions was 96.18%. The adsorption capacity was determined from the adsorption isotherm according to the Langmuir and the freundlich models. The adsorption isotherm model of Cu (II) of teak sawdust follows the Langmuir isotherm model with a maximum adsorption capacity (qmax) of 2.058 mg/g.